Residual stress impact on corrosion behaviour of hot and cold worked 2205 duplex stainless steel: A study by X-ray diffraction analysis. (January 2022) - Akinwamide, Samuel Olukayode; Venter, Andrew; Akinribide, Ojo Jeremiah; Babalola, Bukola Joseph; Andrews, Anthony; Olubambi, Peter Apata
Highlights: 2205 stainless steel is fast replacing other grades of stainless steel. Compressive stress is dominant in the austenite phase. Dislocation accumulation around the grain boundary resulted in increased corrosion. Residual stress promotes the formation of pits. Abstract: The use of 2205 duplex stainless steel (2205 DSS) in the petrochemical and nuclear industries is fast replacing carbon steel and other convectional alloys due to its excellent corrosion resistance and improved mechanical properties it offers. The effect of residual stress on corrosion behaviour of hot and cold rolled 2205 DSS in a chloride environment is investigated. As received hot and cold rolled duplex stainless-steel samples were characterized using a scanning electron microscope (SEM) for microstructural phase analysis. Residual stresses of varying percentages (20, 40, and 60%) were applied to duplex stainless steel samples machined to micro tensile dimensions. The residual stress analysis of the necked region was analyzed using Bruker D8 Advance X-ray diffractometer, while potentiodynamic polarization was carried out in 3.5 wt% NaCl to access the corrosion integrity of the necked region. The center and average principal stress analysis (S11 and S22) of hot and cold-rolled stainless steel in the necked region showed the deformation of austenite and ferrite phases due to tensile pulling with more tensile stress in the austenite phase. SEM micrographs of corrosion substrates revealed the dominance of corrosion in the austenite phase within the necked region in hot rolled samples.